Identity, Power, and Property: an analysis of storefronts by semiotics of culture - Feitosa, Mateus Francisco; Maranhão, Ana Carolina Kalume; Duarte, Pedro Davi Russi (DAT Journal, 2024)
The present work aims to undertake an analysis of sponsored storefronts in the axis between the cities of Goiânia and Alexânia through the semiotics of culture in a decolonial bias, from the modernity/coloniality group. It is assumed that these storefronts are inserted in the visual construction of culture by design. To this end, the semiotics of culture was used as a method of analysis and an element of connection between culture, colonialism and modernity. The results show a Eurocentric view based on the power relations between sponsor and sponsored, reflected in most of the storefronts found in the cities surveyed.